Impact of power and contact force in ablation-index guided radiofrequency lesions in an in vitro model. (24th May 2021) - Lozano-Granero, C; Franco Diez, E; Matia Frances, R; Hernandez-Madrid, A; Sanchez Perez, I; Zamorano Gomez, JL; Moreno Planas, J
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Electrophisiology Section of the Spanish Society of Cardiology Introduction. Lesion Size Index (LSI) and Ablation Index (AI) are markers of lesion quality that incorporate power, contact force (CF), and time in a weighted formula to estimate lesion size. Although accurate predicting lesion depth in-vitro, their precision in lesion size estimation has not been well established for certain power and CF settings. Purpose. We conducted an experimental ex-vivo study to analyse the effect of power and CF in size and morphology of ablation lesions in a porcine heart model. Methods. 24 sets of 10 perpendicular epicardial radiofrequency applications were performed with two commercially available catheters (TactiCath, Sensor Enabled; and SmartTouch) on porcine left ventricle submerged in 37ºC saline, combining different power (25, 30, 35, 40, 50 and 60W) and CF (10 and 20g) settings, and aiming at a lower (LSI/AI of 5/400) or higher (LSI/AI of 6/550) index. After each application, lesions were cross-sectioned and measured. Results. 480 lesions were performed. For a given target index and CF, significant differences in lesion volume and depth with different power settings were observed with both catheters. Regarding lesion volume, statistically significant differences were observed with all CF and LSI targets with TactiCath, except for 10 g and LSI 5 (10 g and LSI 5, p = 0.4134; 10 g and LSI 6, p < 0.0001; 20 g and LSI 5, p < 0.0001; 20 g and LSI 6, p < 0.0001). The same occurred for SmartTouch, showing statistically significant differences with all CF and AI targets, except for 20 g and AI 550 (10 g and AI 400, p = 0.0001; 10 g and AI 550, p < 0.0001; 20 g and AI 400, p < 0.0001; 20 g and AI 550, p = 0.001). Similar differences could be found in lesion depth with each catheter. Globally, lesions performed with 50 and 60W were significantly smaller and shallower than those performed with 35 or 40W (figure). Regarding CF, catheters behaved differently: lesions performed with 10g were smaller and shallower than those performed with 20g with Tacticath, while being bigger and deeper with SmartTouch. In a side-by-side comparison, lesions performed with TactiCath were smaller and shallower than those performed with SmartTouch when applying a lower CF of 10g, both when targeting a lower index objective (volume: 41.8 ± 54.3mm3 vs 158.3 ± 33.2mm3, p < 0.0001; depth: 2 ± 1.7mm vs 4.6 ± 0.5mm, p < 0.0001) or a higher index objective (volume: 103.1 ± 56.5mm3 vs 280 ± 54mm3, p < 0.0001; depth: 4 ± 1.1mm vs 5.8 ± 0.5mm, p < 0.0001). However, lesions with TactiCath were bigger and deeper when applying a higher CF of 20g aiming at a lower index objective (volume: 123.8 ± 39.9mm3 vs 89.7 ± 29.4mm3, p < 0.0001; depth: 4 ± 0.8mm3 vs 3.6 ± 0.5mm, p < 0.0001). No statistically significant difference was observed when applying a higher CF of 20g aiming at a higher index objective. Conclusions. Size and morphology of index-guided radiofrequency lesions varied significantly with different power and CF settings, highlighting the importance of achieving a good CF in any ablation procedure.